2019
DOI: 10.3390/plants8030076
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Genes Related to Sugar and Amino Acid Transport and Cytokinin Metabolism during Leaf Development and Senescence in Pisum sativum L.

Abstract: Gene editing is becoming the plant breeding tool of choice, but prior to targeting a gene for editing, a knowledge of the gene family members (GFMs) controlling yield is required in the specific crop plant. Critical to yield are components from senescing leaves. We targeted genes controlling senescence in Pisum sativum and the release and transport of carbohydrates and amino acids from the source leaves to the pods and seeds. The expression of GFMs for cytokinin biosynthesis (IPT) and destruction (CKX), sucros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 65 publications
1
20
0
Order By: Relevance
“…The experiment was repeated twice as described in Dhandapani et al (2017) and the averaged fold-change values presented for each time point and tissue. The reference genes GAPDH and 18S rRNA were used as internal controls to normalize the data following the procedure used by Song et al (2012) and Ninan et al (2019). As the data derived from the two independent experiments were so consistent the experiment was not repeated a third time.…”
Section: Methodsmentioning
confidence: 99%
“…The experiment was repeated twice as described in Dhandapani et al (2017) and the averaged fold-change values presented for each time point and tissue. The reference genes GAPDH and 18S rRNA were used as internal controls to normalize the data following the procedure used by Song et al (2012) and Ninan et al (2019). As the data derived from the two independent experiments were so consistent the experiment was not repeated a third time.…”
Section: Methodsmentioning
confidence: 99%
“…Those in Cluster 4B including AtAAP1, are necessary for phloem loading and/or seed development (Sanders et al 2009;Santiago and Tegeder 2016), whereas the function of the GFMs in Cluster 1 has yet to be determined. Pea has multiple copies of AAPs, which are distributed in three gene clusters (1, 3A, and 4B) (Dhandapani et al 2017), with expression throughout the plant (Tegeder et al 2007;Ninan et al 2017Ninan et al , 2019.…”
Section: Introductionmentioning
confidence: 99%
“…Cytokinins enhanced mRNA accumulation of hexose transporter genes to supply carbohydrates to sink tissues (Roitsch and Ehneß, 2000). Studies have reported that cytokinins involve in amino acid transport and phosphate and potassium homeostasis by controlling the expression of related transporters or signaling genes (Wang et al, 2006;Nam et al, 2012;Ninan et al, 2019). Altogether, these findings indicate that chloroplast genesis and nutrient transport in OsCKX2 OE rice may be defective, which were detrimental to the assimilation, translocation, and distribution of nutrients.…”
Section: Discussionmentioning
confidence: 96%